Modified Disk-Shaped Compact Tension Test for Measuring Concrete Fracture Properties - Héctor Cifuentes; Miguel Lozano; Táňa Holušová; Fernando Medina; Stanislav Seitl; Alfonso Fernández-Canteli (International Journal of Concrete Structures and Materials, 2017)
Abstract A new approach for measuring the specific fracture energy of concrete denoted modified disk-shaped compact tension (MDCT) test is presented. The procedure is based on previous ideas regarding the use of compact tension specimens for studying the fracture behavior of concrete but implies significant modifications of the specimen morphology in order to avoid premature failures (such as the breakage of concrete around the pulling load holes). The manufacturing and test performance is improved and simplified, enhancing the reliability of the material characterization. MDCT specimens are particularly suitable when fracture properties of already casted concrete structures are required. To evaluate the applicability of the MDCT test to estimate the size-independent specific fracture energy of concrete (G F ), the interaction between the fracture process zone of concrete and the boundary of the MDCT specimens at the end of the test is properly analyzed. Further, the experimental results of G F obtained by MDCT tests for normal- and high-strength self-compacting concrete mixes are compared with those obtained using the well-established three-point bending test. The procedure proposed furnishes promising results, and the G F values obtained are reliable enough for the specimen size range studied in this work.